Changing Pattern of P and QRS Waves of Electrocardiogram among the Different Grades of Hypertensive Patient of Bangladesh (Journal of Current and Advance Medical Research, 2018)
Background: Determination of the electrocardiographic changes among the hypertensive patients can reveal the early cardiac abnormalities especially of left ventricular hypertrophy.Objectives: The purpose of the present study was to find out the P and QRS waves of electrocardiographic (ECG) changes in different grades of hypertensive patients.Methodology: This cross sectional study was conducted among mild to severe grade hypertensive patients attended in the Department of Medicine at Rajshahi Medical College and Hospital, Rajshahi during the period of July 2009 to June 2010 for a period of one year. Data were collected by face to face interview with a pre-designed structured questionnaire. Measurement of the blood pressure and the 12-lead surface electrocardiogram were done among the study group in a resting state.Results: A total number of 400 hypertensive patients were recruited for this study. In mild hypertension, high voltage QRS complex was noted as the main ECG abnormality (24.8%) which was followed by wide P-wave (15.2%). In moderate hypertension, the high voltage QRS complex was 31.0%, wide P wave 25.0%. In severe hypertension, wide P wave and high voltage QRS complex were 56.0%and 20.0% cases respectively. Chi-square test was done between category of hypertension and ECG changes of the study group. The results were statistically highly significant (p